Advances in human factors and system interactions : proceedings of the AHFE 2017 International Conference on Human Factors and Systems Interaction, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors and Systems Interaction, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available